2010
DOI: 10.1002/pc.21035
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐scale hybrid composites‐based carbon nanotubes

Abstract: Since the carbon nanotubes (CNTs) have been discovered, there has been a marked increase in the scientific literature dealing with multi-scale composites. The multi-scale hybrid composites with CNTs could endow the composites with some superior mechanical properties, such as improving the tensile performance, modest increasing compressive and flexural properties, and significantly enhancing interlaminar, interfacial and fracture strength. In addition, composites with CNTs can also develop the functional proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 97 publications
0
14
0
Order By: Relevance
“…Such type of composites containing mixtures of microscale fibers and nanoscale fillers in a polymeric matrix is called multiscale composites . The introduction of nanofillers with micro‐fiber reinforcement in a polymeric matrix can be obtained by dispersing the nanofillers in the matrix or reinforcing of fibers through growing of nanofillers on their surfaces . Shokrieh et al evaluated the influence of adding multi‐walled carbon nanotubes (MWCNTs) at various contents on the tensile and flexural behaviors of chopped strand mat/polyester composites and reported that adding only 0.05 wt% MWCNTs increased the flexural strength of the multiscale composite by 45% while the tensile strength was not changed significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Such type of composites containing mixtures of microscale fibers and nanoscale fillers in a polymeric matrix is called multiscale composites . The introduction of nanofillers with micro‐fiber reinforcement in a polymeric matrix can be obtained by dispersing the nanofillers in the matrix or reinforcing of fibers through growing of nanofillers on their surfaces . Shokrieh et al evaluated the influence of adding multi‐walled carbon nanotubes (MWCNTs) at various contents on the tensile and flexural behaviors of chopped strand mat/polyester composites and reported that adding only 0.05 wt% MWCNTs increased the flexural strength of the multiscale composite by 45% while the tensile strength was not changed significantly.…”
Section: Introductionmentioning
confidence: 99%
“…The composites, which are light in weight, high in strength, and can be manufactured according to the required performance, have been accepted in industrial fields. With the rapid development of aerospace, composites have been one of the four structural materials after aluminum, steel, and titanium materials . At present, both the macro‐ and micro‐mechanical methods are used to analyze the mechanical behaviors of composite structures .…”
Section: Introductionmentioning
confidence: 99%
“…Examples include structural members in the aerospace industry, low‐energy sensing materials for dimethyl methylphosphonate (DMMP), a nerve gas stimulant , and lubricants with enhanced tribological and thermal properties. Other potential applications include wire and cable applications in the aerospace and energy exploration sectors , permeable membranes in electromagnetic induction shielding, and biomolecule and drug delivery , to name but a few.…”
Section: Introductionmentioning
confidence: 99%